Analisis Struktur dan Makna dalam Cerpen “Negosiasi Hati dan Pikiran (Chemistry Kisah Mistis Hidupku)” Karya Uji Saputro: Structural and Meaning Analysis in The Short Story “Negotiation Of Heart And Mind (Chemistry Of My Mystical Story Of Life)” By Uji Saputro - Fahlia, Jeni Sinta; Rifai, Ahmad; Utami, Hadi Riwayati (Universitas Tidar, 2025)
This study aims to describe the narrative structure and interpret the meaning contained in the short story “Negosiasi Hati dan Pikiran (Kisah Mistis Hidupku)” by Uji Saputro. The story presents a personal journey marked by inner conflict and mystical experiences, told from a first-person point of view that explores the struggle between the mind, heart, and physical endurance. The research focuses on how the story’s structure is composed and what meanings can be interpreted from it. This study uses a descriptive qualitative method. The story features a dynamic plot, complex characters, emotional settings, and a first-person perspective that enhances reader engagement. In terms of meaning, the short story illustrates an internal negotiation between heart, mind, and body in facing life pressures and mystical experiences. This process symbolizes the search for identity, the balance between logic and emotion, and the effort to achieve inner peace. Overall, the story not only delivers a touching personal narrative but also offers a philosophical reflection on how humans overcome inner crises through strength from within.